The skill qualification system for portal hypertension in Japan. Issue 1 (25th November 2021) - Ohta, Masayuki; Murashima, Naoya; Ohyama, Tetsuji; Yoshida, Tomoharu; Hirota, Shozo; Kawanaka, Hirofumi; Hashizume, Makoto; Nakamura, Shinichi; Chikamori, Fumio; Eguchi, Susumu; Tajiri, Takashi; Obara, Katsutoshi; et al.
Abstract: Objectives: The diverse treatments available for portal hypertension require specialized knowledge of hemodynamics and include endoscopic treatments, interventional radiology (IVR), and surgery. The Japan Society for Portal Hypertension has developed the skill qualification system (SQS) for portal hypertension and began examination in 2014. Here, the status and validity of the judgment of the SQS examination were evaluated. Methods: From 2014 to 2020, 79 applicants were evaluated by the SQS for portal hypertension. Each unedited video submitted as a candidate procedure was evaluated by two judges, and a grade of greater than 70% for the scoring items assessed by the judges was required to pass the examination. Inter‐rater agreement of success/failure between the two judges was investigated by the AC1 coefficient. Results: The results of two judges differed for 11 of the 79 videos (13.9%), and five applicants (6.3%) ultimately failed the examination. The percentages of total points received by the applicants with endoscopic treatments, IVR, and surgery were 87.3%, 79.4%, and 80.8%, respectively. There were significant differences in the percentages between endoscopic treatments and IVR ( P = 0.0015). The AC1 coefficients were 0.84 for the applicants overall, 0.93 for endoscopic treatments, 0.66 for IVR, and 0.72 for surgery. Similarly, there were significant differences in the AC1 coefficient between endoscopic treatments and IVR ( P = 0.021). Conclusions: The SQS for portal hypertension of the Japan Society for Portal Hypertension showed high reliability for video assessments by the judges. This system may contribute to the spread and further development of safe and effective treatments for portal hypertension in Japan.